RESEARCH AND DEVELOPMENT OF AN INTELLIGENT CRM FOR FOODSERVICE ENTERPRISES WITH A DIGITAL TWIN FOR OPERATIONS SIMULATION AND OPTIMIZATION - Umarov , Umarxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This study presents the research, design, and development of an Intelligent Customer Relationship Management (CRM) platform enhanced with a Digital Twin to support operational simulation and optimization within foodservice enterprises. The system integrates dynamic analytics, workflow monitoring, and data-driven decision support while the Digital Twin replicates operational workflows using agent-based and discrete-event simulation. Evaluation results demonstrate improved throughput, reduced waiting times, and enhanced predictive accuracy across foodservice operations.